Studies of the species barrier between Drosophila madeirensis and Drosophila subobscura. II. Genetic analysis of developmental incompatibilities in hybrids - Khadem, Mahnaz (2021)
The genetic analysis of two abnormal Characters, extra sex combs and abnormal head shape in hybrids between Drosophila madeirensis and Drosophila subobscura, revealed a major effect of the X chromosome in both cases. Autosomes also play a role in determining these abnormalities, the E chromosome in case of extra sex combs, the E and 0 chromosomes in case of abnormal head shape. Autosomes do not cause the two abnormal characters, without interacting with the X chromosome.